Para uma ética da amizade em Friedrich Nietzsche - Oliveira, Jelson Roberto de (2009)
This work aims to analyze the Nietzsche s project of an ethics of friendship, as it appears in the writings of the so-called second period of the production of the German philosopher (1876-1882). We begin with the hypothesis that the Nietzsche s philosophy undertaking must be understood as an experimental process that aims to overthrow the metaphysical foundations of the philosophy, art and religion to reveal a affirmative and original intent of morality in which the individual's self appears as main theme. This moral of the individuality, however, relies on the notion of friendship because the individual is understood by Nietzsche as a multiple and constituted from the basis of relations among their peers, whose result is the assertion of life. Objects to the morality of compassion for this lead to the denial of the existence abnegation of the individual and their submission to the fellow man, the German philosopher recovers the notion of friendship as antidote to the decadence of modern relationships, whose balance is the rise of the absolute value of equality gregarious and the consequent illness of the human. The assertion of himself and of the reality are the foundations of a type of thinking that connects the morality to individual pathos which is constructing the shaft from the experimental and obtain as result not a canon of values, but the freedom of spirit and happiness tragic-existential. This hypothesis will require an analysis of methodological assumptions that mark the thought of Nietzsche in this second period, summarized under the concept of experimentalism. In the first chapter of this work is carried out an examination of the experimental procedure and the use of this stratagem for analysis of life and human phenomenon, which leads to the relationship between loneliness, illness and friendship as a privileged space for experimenting with the individual with himself. The three following chapters deal with the Nietzsche's critical of the foundations of the ethics of compassion and then be listed the two devices that characterize the design his project of the ethics of friendship: freedom of spirit and sharing of happiness.The notion of freedom of spirit encompasses some of the virtues of his moral of the future: the courage of detachment, the simplicity that make possible the nomadic life of the stroller and strength of the enemy. The sharing of happiness refers, in turn, the concept of life as celebration, virtue of the laughter and a sense prophylactic of the Mitfreude, which opposed to the compassion (Mitleide) presents itself as a congratulation (Mitfreunde).